2016
DOI: 10.1142/s1793545816500267
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the penetration and accumulation of gold nanoparticles in rat skin ex vivo using surface-enhanced Raman scattering spectroscopy

Abstract: Contamination by accidental cutaneous contact with the commercial products and the air pollutants raised a considerable health and safety issue. This study aimed to trace the dynamics of the 20 nm gold nanoparticle (GNP) penetration and accumulation in rat skin tissues using a surface-enhanced Raman scattering (SERS) technique. After the topical application of GNPs on rat skin surface, the SERS spectra were recorded for every 15 m to an overall depth of 75 m from skin surface for 150 min. The processes of GNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Penetration and accumulation of gold nanoparticles can be also monitored using a surfaceenhanced Raman scattering (SERS) technique. Therefore, SERS spectroscopy has the potential to monitor the dynamics of nanoparticle penetration and accumulation within the tissues [116].…”
Section: Genotoxicity and Mutagenicitymentioning
confidence: 99%
“…Penetration and accumulation of gold nanoparticles can be also monitored using a surfaceenhanced Raman scattering (SERS) technique. Therefore, SERS spectroscopy has the potential to monitor the dynamics of nanoparticle penetration and accumulation within the tissues [116].…”
Section: Genotoxicity and Mutagenicitymentioning
confidence: 99%
“…A number of studies have used several analytical and imaging techniques to investigate the dermal penetration potential of NM and have shown a limited ability for nAu and nTiO 2 to penetrate the skin in vivo and in vitro . In these studies, NM were detected by silver staining, surface enhanced Raman spectroscopy, mass spectroscopy and electron microscopy, and electron microscopy energy dispersive X-ray analysis, with no evidence for transdermal penetration. Sadrieh et al reported the presence of nTiO 2 particles in the dermis following a sub chronic dermal exposure in mini pigs; however, contamination during sample preparation, or cross contamination between samples, could not be ruled out .…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of SERS-active silver [ 148 , 223 , 257 ] and gold [ 258 , 259 ] nanoparticles has been successfully studied by tracking the appearance of the SERS signal at a certain skin depth. The release of coated silver nanoparticles within the skin has also been demonstrated by the appearance of the SERS spectra [ 148 , 223 ], whose shape and intensity are very different from the spontaneous Raman scattering spectrum of intact skin ( Figure 7 D).…”
Section: Surface-enhanced Raman Scattering (Sers) Microscopymentioning
confidence: 99%